Long Term Management of Rhizomania Disease—Insight Into the Changes of the Beet necrotic yellow vein virus RNA-3 Observed Under Resistant and Non-resistant Sugar Beet Fields - Galein, Yann; Legrève, Anne; Bragard, Claude (Frontiers in Plant Science, 2018)
Rhizomania disease, caused by the Beet necrotic yellow vein virus, is considered as one of the major constraints for sugar beet production, worldwide. As a result of the introgression of major resistance genes (Rizor, Holly, Rz2) in commercially available sugar beet varieties, the virus has endured strong selection pressure since the ’90s. Understanding the virus response and diversity to sugar beet resistance is a key factor for a sustainable management of only few resistance genes. Here we report rhizomania surveys conducted in a rhizomania hot spot, the Pithiviers area (France) during a four-year period and complementary to the study of Schirmer et al. (2005). To follow rhizomania development over the sugar beet growing season, extensive field samplings combined with field assays were performed in this study. The evolution of the BNYVV diversity was assessed at intra- and inter-field levels, with sugar beet cultivars containing different resistance genes (Rz1, Rz1 + Heterodera schachtii resistance and Rz1Rz2). Intra-field diversity was analyzed at the beginning and the end of the growing season of each field. From more than one thousand field samples, the simultaneous presence of the different A, B and P types of BNYVV was confirmed, with twenty-one variants identified at positions 67–70 of the p25 tetrad. The first variant, AYHR, was found most commonly followed by SYHG. Numerous mixed infections (9.93% of the samples), mostly of B-type with P-type, have also been evidenced. Different tetrads associated with the A- or B-type were also found with a fifth RNA-genome component known to allow more aggressiveness to BNYVV on sugar beet roots. Cultivars with Rz1+Rz2 resistant genes showed few root symptoms even if the BNYVV titre was quite high according to the BNYVV type present. The virus infectious potential in the soil at the end of the growing season with such cultivars was also lower despite a wider diversity at the BNYVV RNA3 sequence level. Rz1+Rz2 cultivars also exhibited a lower presence of Beet soil-borne virus, a P. betae-transmitted Pomovirus. Cultivars with Rz1 and nematode (N) resistance genes cultivated in field infected with nematodes showed lower BNYVV titre than those with Rz1 o